Adaptation of the Teacher Self-Efficacy Scale to Azerbaijani: Investigating its Relationship with Work Engagement, Anxiety, and Job Satisfaction - Bakhtiyar Aliyev; Ulkar Zalova Nuriyeva; Elnur Rustamov; Rahila Mammadova; Aysel Naghiyeva; Fatima Dadashzada (Universitas Negeri Semarang, 2025)
Teacher self-efficacy is a central construct influencing instructional practices, classroom management, and student outcomes. Despite its importance, no validated instrument exists in Azerbaijan to assess teachers’ self-efficacy. This study aimed to adapt the Teacher Sense of Efficacy Scale (TSES) into Azerbaijani and examine its psychometric properties. Data were collected from 293 Azerbaijani teachers via an online survey. Confirmatory factor analysis (CFA) supported the original three-factor structure, with acceptable fit indices (χ²/df = 3.283, CFI = .939, TLI = .922, RMSEA = .088). Reliability was evaluated through multiple indices, demonstrating high internal consistency (Cronbach’s α = .925), strong item homogeneity (McDonald’s ω = .926), and robust test-score reliability (Guttman’s λ6 = .930). Item Response Theory (IRT) analyses indicated strong discrimination parameters for all items (α = 1.78–2.91), confirming the scale’s capacity to differentiate teachers with varying efficacy levels. Concurrent validity was supported through positive correlations with work engagement and job satisfaction, and negative correlations with anxiety. Overall, the findings suggest that the Azerbaijani TSES is a psychometrically sound instrument, suitable for research, professional development, and policy applications. This adaptation provides a valuable tool for assessing teacher self-efficacy in Azerbaijani educational contexts, contributing to cross-cultural research and enhancing evidence-based strategies to improve teacher effectiveness and well-being